Phenological Growth Stages According to the BBCH Scale Elaeagnus multiflora Thunb. - Grygorieva, Olga; Ilyinska, Antonina; Zhurba, Mykhailo; Klymenko, Svitlana; Kalista, Mariia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2022)
Phenology is a key trait of plants of all species, as it determines their season and duration of growth and reproduction, as well as their ability to capture variable resources. Understanding the phenology of Elaeagnus multiflora Thunb. a rare but promising fruit and medicinal plant of Ukraine, namely the codification of the stages of seasonal development, according to the international BBCH scale, is important for the evaluation of breeding material and the development of new varieties, improving the technological qualities of fruits. In the climatic conditions of Ukraine (M.M. Gryshko National Botanical Garden of the National Academy of Sciences of Ukraine, Kyiv), the studied genotypes of E. multiflora go through a full cycle of development. Plants begin the growing season with the development of leaves and shoots. According to the international BBCH scale, they clearly distinguish eight of the ten main stages of seasonal development, in particular: the development of buds (Principal growth stage 0), leaves (Principal growth stage 1), shoots (Principal growth stage 3), inflorescence emergence (Principal growth stage 5), flowering (Principal growth stage 6), fruit development (Principal growth stage 7), fruit ripening (Principal growth stage 8) and senescence and the onset of dormancy (Principal growth stage 9). The proposed BBCH scale for characterizing the phenological stages of E. multiflora plants can be used to guide the growers as to when to carry out orchard management practices such as canopy training and pruning, nutrient and water application, pest and disease control and post-harvest processing. Correct identification of phenological stages is of great importance for the characterization and management of E. multiflora. Thus, this study will ensure the dissemination of knowledge about E. multiflora cultivars among growers and researchers.